Carbon nanowire aerogel material as well as preparation method and application thereof

The COF wet gel was synthesized and heat treated by sol-gel method, which solved the problems of uneven pore structure and low mechanical strength in the preparation of carbon nanowire aerogel, and achieved efficient preparation of carbon nanowires with high specific surface area and stable adsorption properties. Aerogel improves its performance in the fields of supercapacitors and adsorption.

CN119284884AActive Publication Date: 2025-01-10YANTAI UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411413482.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing carbon nanowire aerogel preparation methods are complex, with high cost, high energy consumption, uneven pore structure and low mechanical strength, resulting in unstable adsorption performance and insufficient supercapacitor performance.

Method used

The COF wet gel was synthesized by sol-gel method, and carbon nanowire aerogel was obtained through solvent thermal reaction and freeze-drying. The reaction conditions were controlled to achieve structural and performance regulation, including the use of 2,5-diaminobenzonitrile and di- A specific ratio of di-tert-butyl carbonate, 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde and trifluoroacetic acid was solvothermal reaction, and a carbon nanowire aerogel was obtained by solvent replacement and heat treatment.

Benefits of technology

The preparation of carbon nanowire aerogels with high specific surface area, uniform pore structure and high mechanical strength was achieved, which significantly increased the adsorption amount of toluene steam and the capacitance value of supercapacitors, and improved the stability and application potential of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284884A_ABST
    Figure CN119284884A_ABST
Patent Text Reader

Abstract

The invention provides a carbon nanowire aerogel material as well as a preparation method and application thereof, and belongs to the technical field of aerogel preparation. The preparation method comprises the following steps: firstly synthesizing a covalent organic framework (COF) precursor substance, then converting the covalent organic framework (COF) precursor substance into COF wet gel, and finally obtaining the carbon nanowire aerogel material through solvent replacement, freeze drying and high-temperature heat treatment. The process is simple to operate, and the prepared material is controllable in structure; and when the relative pressure is 1, the carbon nanowire aerogel material prepared by the method disclosed by the invention can adsorb 1200 mg / g of toluene steam. In addition, when the prepared carbon nanowire aerogel material is used as a supercapacitor electrode material, the capacitance value at the scanning speed of 20 mV / s is 215 F / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel preparation, and in particular relates to a carbon nanowire aerogel material and a preparation method and application thereof. Background Art

[0002] As an advanced porous carbon material, carbon nanowire aerogel exhibits many unique properties, indicating that it has a wide range of application potential in many fields. First of all, its high specific surface area and porous structure provide a unique platform for adsorption, catalysis and even energy storage. This structural characteristic not only makes carbon nanowire aerogel an ideal choice for adsorbing harmful compounds and as a catalyst carrier, but also gives it great application prospects in the field of supercapacitors. In terms of supercapacitors, the high specific surface area and porous structure of carbon nanowire aerogel greatly promote the rapid diffusion and effective contact of ions in the electrolyte, increasing the capacity and rate of charge storage. These characteristics enable aerogel electrodes to provide higher energy density and power density, and are one of the key materials for realizing high-performance supercapacitors. At the same time, its excellent adsorption capacity allows carbon nanowire aerogel to perform well in environmental protection fields such as air purification and water treatment, and can effectively remove pollutants in the air and harmful substances in the water. As a catalyst carrier, its structural advantages promote the efficiency and selectivity of catalytic reactions, further broadening its application range in the chemical industry. In summary, carbon nanowire aerogel, with its unique structure and properties, has shown great application potential and value in many fields such as supercapacitors, environmental protection, and catalytic reactions, providing innovative solutions for solving environmental pollution problems and improving energy storage efficiency.

[0003] However, existing carbon nanowire aerogels and preparation methods have the following problems:

[0004] (1) Most of the reported methods are carbon aerogels, while there are few methods for preparing carbon nanowire aerogels;

[0005] (2) The pore structure of carbon nanowire aerogel is not uniform enough, which leads to the instability of the adsorption performance of carbon nanowire aerogel materials; the specific surface area is small and the adsorption efficiency is low;

[0006] (3) Low mechanical strength and easy breakage limit the durability and service life of aerogels in practical applications;

[0007] (4) Difficulty in controlling pore structure: It is difficult to accurately control the pore structure of carbon nanowire aerogel during the preparation process, which affects its adsorption performance;

[0008] (5) High cost, high energy consumption and long preparation cycle: The preparation of high-quality carbon nanowire aerogels usually requires complex process flows and expensive raw materials, which makes their production cost high; and the preparation of existing carbon nanowire aerogels usually requires multiple steps of chemical treatment and drying, and the entire preparation cycle is long. This not only increases production costs, but also limits its ability to be quickly mass-produced.

[0009] In addition, the prior art also discloses the use of composite aerogels for adsorbing toluene vapor, such as "Wang Wei et al., Preparation of composite aerogels and adsorption test of toluene, 2018" in "Fire Science and Technology". On the one hand, the preparation process of the composite aerogel is cumbersome, which not only increases the production cost, but also makes it difficult to accurately control the pore structure of the composite aerogel; on the other hand, the prepared composite aerogel has low adsorption efficiency for toluene, and its adsorption amount is only 243 mg / g. Similarly, in the field of supercapacitors, although current electrode materials such as activated carbon have a high specific surface area, the uniformity and connectivity of their pore structure are difficult to guarantee, which in turn affects the performance of supercapacitors. Especially in supercapacitor applications that pursue high energy density and long cycle life, the electrochemical properties of existing materials are often difficult to meet the requirements, such as low capacitance and poor cycle stability, which limits their wide application in high-performance energy storage systems.

[0010] Therefore, there is an urgent need to provide a method for preparing carbon nanowire aerogels with a simple preparation process, which can produce a stable and uniform porous structure, a large specific surface area, high mechanical strength, high adsorption to toluene, and excellent supercapacitor performance. Summary of the invention

[0011] In view of the above technical problems, the present invention proposes a carbon nanowire aerogel material and a preparation method and application thereof.

[0012] To achieve the above object, the present invention provides the following technical solutions:

[0013] One of the technical solutions of the present invention:

[0014] A method for preparing a carbon nanowire aerogel material comprises the following steps:

[0015] Adding 2,5-diaminobenzonitrile and di-tert-butyl dicarbonate into an organic solvent, stirring for reaction, separating and purifying, and obtaining a COF precursor;

[0016] The 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, the COF precursor and trifluoroacetic acid are subjected to a solvothermal reaction in a mixed solvent (COF wet gel is obtained at this time); followed by solvent replacement and freeze drying to obtain COF aerogel;

[0017] The COF aerogel is heat-treated to obtain a carbon nanowire aerogel material.

[0018] Beneficial effects: The present invention adopts the sol-gel method to synthesize COF wet gel. This method can be used to prepare it through a simple chemical reaction under solvent thermal conditions; wherein, by synthesizing COF precursor substances and regulating the overall synthesis conditions, the structure and performance of COF aerogel and the final carbon nanowire aerogel material can be precisely regulated to meet the needs of different application scenarios.

[0019] Preferably, the molar ratio of the 2,5-diaminobenzonitrile to di-tert-butyl dicarbonate is 1:2 to 1:8;

[0020] The usage ratio of the 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, the COF precursor and trifluoroacetic acid is 2 mmol:3 mmol:20 μL.

[0021] Beneficial effect: A uniform COF wet gel can be formed under the above-mentioned reactant types and their dosage ratio conditions specified in the present invention; if the reactant types and dosage ratios specified in the present invention are not adopted, it will be unfavorable for the formation of COF wet gel, and even lead to the inability to obtain nanowire structured materials.

[0022] Preferably, the organic solvent is tetrahydrofuran, ethyl acetate or acetone.

[0023] Beneficial effect: The present invention selects tetrahydrofuran, ethyl acetate or acetone as the organic solvent, which can effectively improve the separation purity; if other solvents are used, the separation purity will be adversely affected.

[0024] Preferably, the stirring reaction time is 8 to 12 hours; the stirring speed is 500 to 1000 rpm.

[0025] Preferably, the separation and purification comprises distillation and recrystallization.

[0026] Furthermore, the recrystallization is as follows: dissolving the bottom product after the distillation with dichloromethane, adding petroleum ether to precipitate the solid and filtering and separating the solid.

[0027] Preferably, the mixed solvent is a mixture of dioxane and water, and the volume ratio of the two is 8:1 to 4:1.

[0028] Beneficial effects: The above volume ratio defined in the present invention is conducive to the uniform dispersion of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde and COF precursor.

[0029] Preferably, the specific operation of the solvent replacement is: replacing the product after the solvent thermal reaction with tetrahydrofuran and tert-butanol in sequence.

[0030] Beneficial effects: The present invention helps to remove residual solvents through replacement of tetrahydrofuran and tert-butyl alcohol and freeze-drying treatment, while maintaining the pore structure of COF aerogel, thereby improving the stability and operability of the material.

[0031] Furthermore, the tetrahydrofuran needs to be replaced 4 times continuously; and the tert-butanol needs to be replaced 3 times continuously.

[0032] Preferably, the solvothermal reaction conditions are: performing the solvothermal reaction at 120° C. for 72 hours.

[0033] Beneficial effects: The present invention is conducive to the formation of COF wet gel by conducting a solvent thermal reaction at 110-180° C. for 24-72 hours.

[0034] Preferably, the heat treatment conditions are: heat treatment at 600-1000° C. for 1-3 hours.

[0035] Beneficial effect: The present invention converts COF aerogel into carbon nanowire aerogel material through high-temperature heat treatment. The method is simple and efficient and can achieve the conversion of COF aerogel into carbon nanowire aerogel in a relatively short time.

[0036] The second technical solution of the present invention:

[0037] The carbon nanowire aerogel material is prepared by the above preparation method.

[0038] Preferably, the specific surface area of ​​the carbon nanowire aerogel material is 910-1032 m 2 g -1 ; pore volume is 1.1-1.3cm 3 / g; density is 145-165mg / cm 3 .

[0039] The third technical solution of the present invention:

[0040] Application of the above carbon nanowire aerogel material in the field of adsorbing toluene vapor.

[0041] Preferably, when the relative pressure is 1, the adsorption capacity of the carbon nanowire aerogel material for toluene vapor is 1200 mg / g.

[0042] The fourth technical solution of the present invention:

[0043] Application of the above carbon nanowire aerogel material in the field of supercapacitors.

[0044] Preferably, when the carbon nanowire aerogel material is used as an electrode material of a supercapacitor, the capacitance value of the supercapacitor is 215 F / g at a scanning speed of 20 mV / s.

[0045] Compared with the prior art, the present invention has the following advantages and technical effects:

[0046] The present invention provides a method for preparing a carbon nanowire aerogel material with a simple process; the prepared carbon nanowire aerogel material also has the characteristics of controllable structure, excellent conductivity (the carbon nanowire aerogel material prepared in Example 1 is 100S / m) and large surface area, further making it have wide application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0048] Figure 1 This is the X-ray diffraction pattern of the carbon nanowire aerogel prepared in Example 1 of the present invention;

[0049] Figure 2 This is the nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Example 1 of the present invention;

[0050] Figure 3 This is a scanning electron microscope image of the carbon nanowire aerogel prepared in Example 1 of the present invention;

[0051] Figure 4 This is a physical picture of the carbon nanowire aerogel prepared in Example 1 of the present invention;

[0052] Figure 5 This is a graph showing the adsorption and desorption curve of pure toluene vapor at 25° C. for the carbon nanowire aerogel prepared in Example 1 of the present invention;

[0053] Figure 6 This is an X-ray photoelectron spectrum of the carbon nanowire aerogel prepared in Example 1 of the present invention;

[0054] Figure 7 This is the cyclic voltammetry curve of the carbon nanowire aerogel prepared in Example 1 of the present invention;

[0055] Figure 8 This is the nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Example 2 of the present invention;

[0056] Fig. 9 This is the nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Example 3 of the present invention;

[0057] Fig.10 This is a cyclic test of the carbon nanowire aerogel prepared in Example 3 of the present invention for the adsorption of pure toluene vapor at 25°C;

[0058] Fig.11 This is the X-ray photoelectron spectrum of the carbon nanowire aerogel prepared in Comparative Example 1;

[0059] Fig.12 is the nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Comparative Example 1;

[0060] Fig.13 This is the adsorption-desorption curve of pure toluene vapor at 25°C for the carbon nanowire aerogel prepared in Comparative Example 1. DETAILED DESCRIPTION

[0061] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0062] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0063] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0064] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0065] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0066] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0067] The raw materials used in the present invention are all purchased from the market.

[0068] The technical solution of the present invention is further illustrated by the following embodiments.

[0069] Example 1

[0070] (1) 2,5-diaminobenzonitrile (10 mmol) was added to a 250 mL round-bottom flask, followed by 100 mL of tetrahydrofuran and 8.73 g (40 mmol) of di-tert-butyl dicarbonate, and the mixture was stirred at 600 rpm for 12 h at room temperature;

[0071] (2) After the reaction, tetrahydrofuran is distilled off, and the bottom product is dissolved with dichloromethane, and then a large amount of petroleum ether is added to precipitate the solid, and the solid product is separated by filtration. The solid product is a COF precursor;

[0072] (3) 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (0.06 mmol) and the above-isolated solid product (0.09 mmol) were added to a 25 mL vial; 3.40 mL of dioxane and 0.60 mL of water were added thereto, and the mixture was mixed by ultrasound (ultrasonic frequency was 250 W, time was 30 min) and 60 μL of trifluoroacetic acid was added; the mixture was then subjected to solvent thermal reaction in an oven at 120° C. for 72 h to obtain a COF wet gel;

[0073] (4) The obtained COF wet gel was replaced with tetrahydrofuran 4 times and tert-butanol 3 times, and then freeze-dried at -50°C for 48h to obtain COF aerogel;

[0074] (5) The COF aerogel was heat treated in a tubular furnace at 800°C for 2 h to obtain a carbon nanowire aerogel material.

[0075] Figure 1This is the X-ray diffraction pattern of the carbon nanowire aerogel prepared in Example 1 of the present invention; from the X-ray diffraction data, the diffraction peak at 26° corresponds to the (002) crystal plane of the graphitized carbon material. This indicates that there is a certain degree of graphitized carbon structure in the sample. The diffraction peak near 44° corresponds to the (100) crystal plane, which is also one of the characteristic peaks of the graphitized carbon material. This XRD pattern shows that there is a certain degree of graphitized carbon structure in the carbon nanowire aerogel sample, but it also contains a large amount of amorphous carbon. Among them, the graphitized carbon has a highly ordered hexagonal layered structure, which can provide a large specific surface area and a stable pore structure; and the graphitized carbon structure has an ordered micropore and mesoporous structure, and these pores contribute to the efficient adsorption of toluene vapor molecules; in addition, the graphitized carbon structure has good cycle stability and shows good durability in repeated adsorption-desorption cycles. The pore structure of amorphous carbon can provide a large specific surface area, which helps to improve the total adsorption capacity. Therefore, the carbon nanowire aerogel prepared in Example 1 of the present invention has both graphitized carbon structure and amorphous carbon structure. This combination can provide a material with both highly ordered pores and a large specific surface area, which can improve the adsorption effect of toluene vapor.

[0076] Figure 2 This is the nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Example 1 of the present invention. As can be seen from the figure, the specific surface area of ​​the carbon nanowire aerogel is about 1030m 2 g -1 .

[0077] Figure 3 This is a scanning electron microscope image of the carbon nanowire aerogel prepared in Example 1 of the present invention; under a high magnification (50.0k times), Figure 3 It can be seen that the carbon nanowires present a mesh structure, interweaving with each other to form a three-dimensional network.

[0078] It can also be seen that:

[0079] 1. The diameter of carbon nanowires is very small, usually ranging from a few nanometers to tens of nanometers.

[0080] 2. The structure of aerogel is highly porous (the pore size of the network composed of nanowires is tens to hundreds of nanometers), and this high surface area characteristic helps it to be used in many fields.

[0081] 3. The connection points and intersections between nanowires give the entire structure a certain degree of mechanical strength and stability.

[0082] Figure 4 This is a physical picture of the carbon nanowire aerogel prepared in Example 1 of the present invention; Figure 4 It can be seen that the aerogel is a black block material. After measurement, its density is 150mg / cm3 .

[0083] Figure 5 This is a graph showing the adsorption-desorption curve of pure toluene vapor at 25° C. for the carbon nanowire aerogel prepared in Example 1 of the present invention (the solid curve represents adsorption, and the hollow curve represents desorption).

[0084] from Figure 5 It can be seen that with the increase of relative pressure, the adsorption capacity of carbon nanowire aerogel for toluene vapor increases significantly, especially at high relative pressure, the adsorption capacity rises rapidly. This shows that carbon nanowire aerogel has a strong adsorption capacity for toluene at high relative pressure. When the relative pressure is close to 1, the adsorption capacity is close to 1200mg / g, which shows that the material has a very high adsorption capacity for toluene.

[0085] Figure 6 This is the X-ray photoelectron spectrum of the carbon nanowire aerogel prepared in Example 1 of the present invention. Figure 6 It can be seen that the carbon nanowire aerogel prepared in Example 1 contains three elements: carbon (C), nitrogen (N) and oxygen (O). The atomic percentage of nitrogen is 8.6%.

[0086] Figure 7 The cyclic voltammetry curve of the carbon nanowire aerogel prepared in Example 1 of the present invention. That is, the electrochemical performance of the material was tested in a 1.0M sulfuric acid electrolyte by a two-electrode method in a voltage range of 0 to 1V. The test electrode contained 85wt.% of active material (i.e., the carbon nanowire aerogel prepared in Example 1), 5wt.% of polytetrafluoroethylene, and 10wt.% of conductive carbon black. Figure 7 It can be seen that when the prepared carbon nanowire aerogel is used as an electrode material for a supercapacitor, the capacitance value is 215F / g at a scanning speed of 20mV / s.

[0087] Example 2

[0088] The difference between this embodiment and embodiment 1 is that the solvent thermal reaction time in step (3) is 24 hours. Other conditions are the same as those in embodiment 1.

[0089] Figure 8 The nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Example 2. As can be seen from the figure, the specific surface area and pore volume of the carbon nanowire aerogel are 910m 2 g -1 and 1.1cm 3 / g. It shows that changing the solvent thermal time has a certain influence on the specific surface area of ​​the carbon nanowire aerogel, but the material obtained within the solvent thermal time range specified by the present invention still has a high specific surface area. The density of the carbon nanowire aerogel is 165mg / cm 3 .

[0090] Example 3

[0091] The difference between this embodiment and embodiment 1 is that the temperature of the tube furnace heat treatment in step (5) is 1000° C. The other conditions are the same as those in embodiment 1.

[0092] Fig. 9 The nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Example 3. As can be seen from the figure, the specific surface area and pore volume of the carbon nanowire aerogel are 980 m 2 g -1 and 1.2cm 3 / g. It shows that the specific surface area of ​​carbon nanowire aerogel is affected by the heat treatment temperature of the tube furnace to a certain extent, but the material obtained within the heat treatment temperature range of the tube furnace defined in the present invention still has a high specific surface area. The density of the carbon nanowire aerogel is 145mg / cm 3 .

[0093] Fig.10 The carbon nanowire aerogel prepared in Example 3 was subjected to a cyclic test on the adsorption of pure toluene vapor at 25°C; Fig.10 It can be seen that the adsorption capacity of toluene vapor by the carbon nanowire aerogel can still reach 1116 mg / g after 6 cycles, indicating that the carbon nanowire aerogel obtained by heat treatment at 1000°C exhibits good durability in repeated adsorption-desorption cycles.

[0094] Example 4

[0095] The difference between this embodiment and embodiment 1 is that the amount of di-tert-butyl dicarbonate in step (1) is 20 mmol. Other conditions are the same as those in embodiment 1.

[0096] Example 5

[0097] The difference between this embodiment and embodiment 1 is that the amount of di-tert-butyl dicarbonate in step (1) is 60 mmol. Other conditions are the same as those in embodiment 1.

[0098] Comparative Example 1

[0099] The difference from Example 1 is that the 2,5-diaminobenzonitrile in step (1) is replaced by p-phenylenediamine. Other conditions are the same as those in Example 1.

[0100] Fig.11 This is the X-ray photoelectron spectrum of the carbon nanowire aerogel prepared in Comparative Example 1. Fig.11It can be seen that the prepared carbon nanowire aerogel contains three elements: carbon (C), nitrogen (N) and oxygen (O). The atomic percentage of nitrogen is 2.9%. This shows that replacing 2,5-diaminobenzonitrile with p-phenylenediamine has a great influence on the nitrogen content of carbon nanowire aerogel.

[0101] Fig.12 is the nitrogen adsorption-desorption isotherm of the carbon nanowire aerogel prepared in Comparative Example 1; Fig.12 It can be seen that the specific surface area of ​​carbon nanowire aerogel is about 340m 2 g -1 It is shown that replacing 2,5-diaminobenzonitrile with p-phenylenediamine has a great influence on the specific surface area of ​​carbon nanowire aerogel.

[0102] Fig.13 The adsorption-desorption curve of pure toluene vapor at 25°C for the carbon nanowire aerogel prepared in Comparative Example 1 (the solid curve represents adsorption, and the hollow curve represents desorption). Fig.13 It can be seen that the adsorption capacity is 480 mg / g when the relative pressure is close to 1. This indicates that replacing 2,5-diaminobenzonitrile with p-phenylenediamine has a great influence on the adsorption amount of toluene vapor of carbon nanowire aerogel.

[0103] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a carbon nanowire aerogel material, characterized in that: The following steps are involved: Adding 2,5-diaminobenzonitrile and di-tert-butyl dicarbonate into an organic solvent, stirring for reaction, separating and purifying, and obtaining a COF precursor; The 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, the COF precursor and trifluoroacetic acid are subjected to a solvothermal reaction in a mixed solvent; and then solvent replacement, freeze drying and heat treatment are performed to obtain a carbon nanowire aerogel material.

2. The method for preparing a carbon nanowire aerogel material according to claim 1, characterized in that: The molar ratio of the 2,5-diaminobenzonitrile to di-tert-butyl dicarbonate is 1:2 to 1:8; The amount ratio of the 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde to the COF precursor is 2:

3.

3. The method for preparing a carbon nanowire aerogel material according to claim 1, characterized in that: The organic solvent is tetrahydrofuran, ethyl acetate or acetone.

4. The method for preparing a carbon nanowire aerogel material according to claim 1, characterized in that: The mixed solvent is a mixture of dioxane and water, and the volume ratio of the two is 8:1 to 4:

1.

5. The method for preparing a carbon nanowire aerogel material according to claim 1, characterized in that: The conditions of the solvent thermal reaction are: conducting the solvent thermal reaction at 110-180° C. for 24-72 hours.

6. The method for preparing a carbon nanowire aerogel material according to claim 1, characterized in that: The specific operation of the solvent replacement is: replacing the product after the solvent thermal reaction with tetrahydrofuran and tert-butanol in sequence.

7. The method for preparing a carbon nanowire aerogel material according to claim 1, characterized in that: The heat treatment conditions are: heat treatment at 600-1000° C. for 1-3 hours.

8. A carbon nanowire aerogel material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. The carbon nanowire aerogel material according to claim 8, characterized in that: The specific surface area of ​​the carbon nanowire aerogel material is 910-1032 m 2 g -1 ; pore volume is 1.1-1.3cm 3 / g; density is 145-165mg / cm 3 .

10. Use of the carbon nanowire aerogel material as claimed in claim 8 or 9 in the field of adsorption of toluene vapor and supercapacitors.

Citation Information

Patent Citations

  • Carbon nanowire material and preparation method thereof

    CN106865538A

  • Fluororubber modified carbon aerogel and preparation method thereof

    CN113617301A

  • Nanowire array modified graphene honeycomb reinforced nano aerogel heat-insulating and wave-absorbing composite material

    CN114656274A

  • Preparation method and application of porous aerogel containing multi-amino three-dimensional graphene

    CN115138342A

  • High-strength aerogel for thermal insulation material and preparation method of high-strength aerogel

    CN115260598A